HUBUNGAN STRES KERJA DENGAN KUALITAS KEHIDUPAN KERJA PERAWAT DI RSUD dr. R. GOETENG TAROENADIBRATA PURBALINGGA: THE RELATIONSHIP OF WORK STRESS AND QUALITY OF WORK LIFE OF NURSES IN RSUD dr. R. GOETENG TAROENADIBRATA PURBALINGGA - Konitasari, Rizky Rofiana; Sumarni, Tri; Kurniawan, Wahyu Eko (BIMIKI (Berkala Ilmiah Mahasiswa Ilmu Keperawatan Indonesia), 2023)
Introduction: Quality of work life is something that a person achieves in his work. When workers' needs fulfilled, it will have a positive impact on increasing organizational productivity. Work stress, in this case, is an environmental change that causes tension that excessively affects physical and psychological conditions. The aim of this research is to understand the relationship between work pressure and the quality of work life that occurs among nurses who work at RSUD dr. R. Goeteng Taroenadibrata Purbalingga. Methods: Quantitative method with a cross sectional approach. The respondents in this study were 96 nurses who met the inclusion criteria. This research uses a probability sampling method that has been adjusted proportionally with the stratified random sampling technique. The reference used in this research is the Expanded Nursing Stress Scale and Quality of Work Life. The statistical analysis used is the Spearman Rank test. Result: The results obtained from data collection shown that the work stress experienced by nurses was mostly in the moderate category (62.5%), and the quality of work life of the nurses was mostly in the high category (53.1%). The result of the overall data analysis is that there is a relationship between work stress and the quality of work life for nurses with a p value of 0.026 (p<a). Conclusion: There is a relationship between work stress and the quality of work life for nurses at RSUD dr. R. Goeteng Taroenadibrata Purbalingga.